Islamic tourism: factors that influence Middle East tourists to choose Malaysia as their choice destination / Norfarahdillah Idris - Idris, Norfarahdillah (Faculty of Business and Management, 2013)
Malaysia as an Islamic country is promoting tourism worldwide in order to attract more tourists to visit Malaysia. Islamic tourism is associated with the various aspects of tourism such as religious, spiritual and cultural. Malaysia is a peaceful and harmonious country of various races and religions. Malaysia also a lot of attractive destinations that are situated in every state in Malaysia. This paper is investigating the factors that influence Middle East tourists to choose Malaysia as their choice destination. The data was collected from books, journals, magazines, websites, questionnaire and documents. Thus, this paper will contribute towards a better understanding about Islamic tourism and Malaysia destinations for tourist.